Marked improvement in gastric involvement in Behçet’s disease with adalimumab treatment - Sonoda, Akira; Ogawa, Ryo; Mizukami, Kazuhiro; Fukuda, Kensuke; Shuto, Mitsutaka; Okamoto, Kazuhisa; Matsunari, Osamu; Okimoto, Tadayoshi; Murakami, Kazunari (Turkish Journal of Gastroenterology, 2017)
Abstract Gastric involvement is the least frequent manifestation of Behçet’s disease, and effective treatment for it unknown. Here the case of a patient with gastric involvement in Behçet’s disease that was markedly improved with adalimumab therapy is presented. A 68-year-old man developed an oral ulcer, erythema, folliculitis, and arthralgia. Behçet’s disease was suspected; then, prednisolone and colchicine were administered. Esophagogastroduodenoscopy showed a punched-out ulcer in the posterior wall of the gastric antrum. Ileocolonoscopy showed multiple punched-out ulcers in the terminal ileum. Capsule endoscopy showed multiple circular ulcers throughout the entire small intestine. A diagnosis of non-steroidal, anti-inflammatory, drug-induced enteritis was made. Withdrawal from diclofenac and initiation of lansoprazole healed the circular ulcers in the small intestine, but were ineffective for the gastric ulcer and punched-out ulcers in the terminal ileum. Eradication of Helicobacter pylori was also ineffective. A diagnosis of gastric involvement of Behçet’s disease was then made, and the gastric ulcer became steroid-dependent. Mesalazine powder was ineffective, and the patient was intolerant to azathioprine.Adalimumab healed the gastric ulcer, and prednisolone was withdrawn. The outcome of the present patient suggests that adalimumab is effective in the treatment of gastric involvement in Behçet’s disease. Cite this article as: Sonoda A, Ogawa R, Mizukami K, et al. Marked improvement in gastric involvement in Behçet’s disease with adalimumab treatment. Turk J Gastroenterol 2017; 28: 405-7.